(untitled) (Scientific journal of the Fergana State University, 2025)
Absract It is known that lyrical works have a lyrical character. That is, in the poem, various experiences and feelings of the creator’s psyche are expressed through the lyrical hero. In literary studies, the study of the lyrical hero in relation to the creative "I am" is considered an important issue. This article discusses the issue of the lyrical hero and the nature of the lyrical "I am" in Usman Azim’s poetry. Based on some of the poet’s poems, the nature of the lyrical hero, harmony with the spirit of the creator will be highlighted. In some of his poems belonging to performance lyrics, artistic analysis shows that the qualities of the creator are instilled in the lyric hero. It is determined that the study of the nature of the lyrical hero occupies an important place in the study of the poetics of the poet’s poetry.